Rights versus crime: Twenty years of wiretapping and digital surveillance in Peru - Gutiérrez, Fabiola (2014)
The systematic monitoring of citizens by the state in Peru was revealed in 2000, after the collapse of the second administration of ex-president Alberto Fujimori (1995-2000). Fujimori resigned in his last year in office, after a network of government espionage and corruption was revealed. This included video recordings of secret meetings and alleged communications surveillance conducted and managed by presidential advisor Vladimiro Montesinos, working with the National Intelligence Service (SIN). This systematic surveillance by the state resulted in the dissemination of private information, recordings and videos of public officials, journalists and many other influential people. These events sparked the beginning of the debate around the purpose of surveillance in Peru, and the violation of the right to private communications by state agencies and private entities – and what legislation could be developed to regulate this. This discussion is ongoing, with more cases of communications interception being revealed.